School-based Standard Testing - Bolon, Craig (Education Policy Analysis Archives, 2000)
School-based standard testing continues to evolve, yet in some ways it remains surprisingly close to its roots in the first two decades of the twentieth century. After use for many years as a diagnostic and as a filter for access to education, in the closing years of the century it has been pressed into service for state-run political accountability programs. In this role, it is generating vehement controversy that recalls protests over intelligence testing in the early 1920s. This background article explores primary characteristics and issues in the development of school-based standard testing, reviews its typical lack of qualification for political accountability programs, and suggests remedies to address major problems. In general, the attitude toward new techniques of assessment is skeptical, in light of the side-effects and unexpected problems that developed during the evolution of current techniques.